CO recovery from blast furnace gas by vacuum pressure swing adsorption process: Experimental and simulation approach. (20th April 2022) - Oh, Hyunmin; Lee, Soobin; Beum, Hee Tae; Kim, Jungil; Kim, Jinsu; Lee, Suh-Young; Lee, In-Beum; Yoon, Young-Seek; Han, Sang Sup
Abstract: This paper presents experimental and numerical approaches to use a four-bed, six-step CO vacuum-pressure-swing adsorption (VPSA) process with CuCl/boehmite adsorbent to extract carbon monoxide (CO) gas from a simulated blast furnace gas (BFG; N2 :CO:CO2  = 60:20:20 mol %) at setting temperature T set  = 60 °C and adsorption pressure 2.5 bar ≤  P ad  ≤ 6.4 bar. The cyclic adsorption isotherms of pure CO2 and CO on CuCl/boehmite pellets were measured at temperature range, 20 °C ≤  T set ≤ 60 °C using a volumetric method. At T set  = 60 °C, the CO-adsorption capacity was stable during cyclic operation, with negligible hysteresis between adsorption and desorption processes. A mathematical model of four-bed, six-step CO-VPSA was developed; this model successfully reproduced the bench-scale experimental data. A sensitivity analysis of the effect of feed flowrate, rinse flowrate, and desorption pressure on CO purity and recovery was conducted to improve the efficiency of the CO enrichment. Simulations show that 79.9–87.4 mol % of CO recovery could be attained with >90 mol % purity of CO, and 71.8–81.8% CO recovery could be achieved with >99 mol % purity of CO at T set  = 60 °C and 2.5 bar ≤  P ad  ≤ 6.4 bar. This method to recover CO from emissions by the steel-making industry can detoxify them, and the CO can be used in syntheses of value-added chemical products. Highlights: A cyclic adsorption isotherm model of CO on CuCl/Boehmite adsorbent is established. A numerical model of CO VPSA process is constructed for CO separation from the Blast Furnace Gas. A sensitivity analysis of the CO VPSA model is conducted to provide an operation guideline.